2014
DOI: 10.1007/s10456-014-9428-3
|View full text |Cite
|
Sign up to set email alerts
|

Intussusceptive angiogenesis: expansion and remodeling of microvascular networks

Abstract: Intussusceptive angiogenesis is a dynamic intravascular process capable of dramatically modifying the structure of the microcirculation. The distinctive structural feature of intussusceptive angiogenesis is the intussusceptive pillar—a cylindrical microstructure that spans the lumen of small vessels and capillaries. The extension of the intussusceptive pillar appears to be a mechanism for pruning redundant or inefficient vessels, modifying the branch angle of bifurcating vessels and duplicating existing vessel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
148
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 196 publications
(156 citation statements)
references
References 61 publications
4
148
0
4
Order By: Relevance
“…A distinguishing anatomic feature of intussusceptive angiogenesis is the intussusceptive pillar, a transluminal tissue bridge that spans the vessel lumen. Physical expansion or growth of the pillar along the vessel axis divides the lumen resulting in vascular duplication [23]. Even though the molecular mechanisms leading to intussusceptive angiogenesis are not fully elucidated, recent observations have shown that inhibition of Notch signaling in already existing vascular beds induces extensive intussusceptive angiogenesis [24].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A distinguishing anatomic feature of intussusceptive angiogenesis is the intussusceptive pillar, a transluminal tissue bridge that spans the vessel lumen. Physical expansion or growth of the pillar along the vessel axis divides the lumen resulting in vascular duplication [23]. Even though the molecular mechanisms leading to intussusceptive angiogenesis are not fully elucidated, recent observations have shown that inhibition of Notch signaling in already existing vascular beds induces extensive intussusceptive angiogenesis [24].…”
Section: Resultsmentioning
confidence: 99%
“…Intussusceptive angiogenesis is distinct from sprouting angiogenesis because it does not require cell proliferation. It might represent a general fast recovery adaption of vascularization to growth necessities with a rapid expansion of the existing microvascular network [23]. In inflammatory tissue, a shift is observed from sprouting angiogenesis toward intussusceptive angiogenesis [23].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These indentations then grow towards each other and finally connect, forming a hollow pillar within the tube that is later invaded by pericytes and myofibroblasts. Finally, neighboring pillars fuse, resulting in longitudinal splitting of the entire vessel (Gianni-Barrera et al, 2014;Mentzer and Konerding, 2014). Intussusception is influenced by blood flow (Djonov et al, 2002), stretching (Belle et al, 2014) and signaling (Baum et al, 2010).…”
Section: Box 2 Intussusception: the Splitting Of Vesselsmentioning
confidence: 99%